Defending rice crop from blast disease in the context of climate change for food security in Nepal - Khadka, Ram Bahadur; Manandhar, Hira Kaji; Shrestha, Sundar; Acharya, Basistha; Sharma, Pratiksha; Baidya, Suraj; Luu, Van Schepler; Joshi, Krishna Dev (Frontiers in Plant Science, 2025)
Blast, caused by Pyricularia oryzae (teleomorph Magnaporthe oryzae), is one of the most devastating diseases in rice, causing 10-30% yield losses and threatening Nepal’s food and nutritional security. The Himalayan foothills are hotspots for blast fungus diversity, leading to the rapid emergence of pathotypes that overcome resistance in mega rice varieties. In 2022, a neck blast epidemic devastated 5,000 hectares of Hardinath-1, a dry winter/spring rice variety in Chitwan, causing nearly 100% yield loss. The changing climate, especially during panicle initiation stages, has become more favourable for neck blast development. We reviewed 40 years of research and development on rice blast in Nepal, analysing historical weather patterns and mapping the incidence and severity of the disease across the country based on empirical observations and field experiments. Using historical data on rice blast incidence and climate information, we show that rice blast pressure is increasing intensively and changing weather patterns are becoming more favourable for rice blast epidemics. We identify emerging issues in rice blast and propose integrated strategies for effective management in Nepal. Key approaches include developing durable blast-resistant and climate-resilient rice varieties using molecular markers and genomic tools and speed breeding, forecasting disease and pathotype emergence, and combining these with careful use of modern fungicides, plant defence activators, and biological control. Additionally, adjusting planting times, managing weeds, optimising agronomic practices, and ensuring proper water and nutrient management are essential for sustainable blast management.